2010
DOI: 10.1007/s13277-010-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new serum biomarkers in breast cancer using lipid microarrays

Abstract: Breast cancer is the most common form of cancer among women. Compared with other serum polypeptides, autoantibodies have many appealing features as biomarkers including sensitivity, stability, and easy detection. Anti-lipid autoantibodies are routinely used in the diagnosis of autoimmune diseases, but their potential for cancer diagnosis has not been explored. Dysregulation of cellular signaling in cancer cells would be expected to lead to irregular metabolism of many lipids, which could be sensed by the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…35,[47][48][49] Some studies have found specific changes in choline metabolism that were linked to more aggressive carcinomas. 50,51 It has been proposed that the altered cellular lipid structure is associated with altered cellular functions, such as protein trafficking, which promotes the onset of cancer or contributes to the progression of the disease. [52][53][54] Measuring phospholipids using mass spectrometry.…”
Section: The Association Of Altered Composition Of Phospholipids and mentioning
confidence: 99%
“…35,[47][48][49] Some studies have found specific changes in choline metabolism that were linked to more aggressive carcinomas. 50,51 It has been proposed that the altered cellular lipid structure is associated with altered cellular functions, such as protein trafficking, which promotes the onset of cancer or contributes to the progression of the disease. [52][53][54] Measuring phospholipids using mass spectrometry.…”
Section: The Association Of Altered Composition Of Phospholipids and mentioning
confidence: 99%
“…Our study is unique compared with previous studies on the discovery of SLE biomarkers. Traditionally, researchers have applied microarrays of whole antigen (protein or lipid) to char-acterize the sera of autoimmune diseases (21,(25)(26)(27)(28). However, these arrays are limited in that they only contain known autoantigens.…”
Section: Discussionmentioning
confidence: 99%
“…Another important criterion is the number of analytes used in a study. In most cases these will be proteins, but lipids, [25][26][27] circulating tumor cells, 28,29 autoantibodies, 25,[30][31][32][33] and microRNAs 21,34,35 have been reported as well. The larger the number of analytes in a study, the larger the sample needed to compensate for multiple comparisons and to minimize false discovery.…”
Section: Marker Discovery In Bloodmentioning
confidence: 99%